A multi-criteria-based ranking of Greek construction companies listed in Athens Stock Exchange using investment ratios. (2018) - Vogiatzis, Pantelis; Aretoulis, Georgios N.; Papathanasiou, Jason
The construction sector has always been one of the main developmental branches of the Greek economy. Building activities and infrastructure projects were the backbone of the construction sector, while other activities from the mining, manufacturing, commerce and services sectors were integrated into the wider supply chain of construction. The aim of the present study is to firstly evaluate the performance and then rank the greatest construction companies, listed in the Athens Stock Exchange, using investment ratios. The research focuses on the period 2004-2014. Four companies are selected that are listed in Athens Stock Exchange and have a construction certificate of the 7th degree for public projects. The applied multi-criteria methodology was PROMETHEE. The latter was implemented using the Visual Promethee software, in order to rank the selected companies. It is concluded that during the period 2004-2008, leading companies are those which their consolidated financial statements outweigh their corporate financial statements, whereas after 2008 when the financial crisis commenced, leading companies are regarded those which their consolidated financial statements are approximate to their corporate financial statements.